Synthesis process of calcium hydrophosphate dihydrate superfine powder

PMMA/PAA nanoparticles with core-shell structures were prepared by fine emulsion polymerization, and calcium and phosphorus ions were adsorbed to form calcium hydrogen phosphate dihydrate shells, which solved the problems of difficult particle size control and high brittleness in the synthesis of calcium hydrogen phosphate dihydrate in the prior art, and achieved the improvement of the toughness and binding strength of ultrafine powder.

CN120554786APending Publication Date: 2025-08-29JIANGXI JINGWEITONG NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510751267.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-06
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The existing calcium hydrogen phosphate dihydrate synthesis methods have problems such as difficulty in controlling particle size, easy introduction of metal wear impurities, low crystallinity of the product, long reaction cycle, high equipment cost, and large energy consumption. The products obtained by chemical precipitation are relatively brittle.

Method used

PMMA/PAA nanoparticles with core-shell structures were prepared by fine emulsion polymerization. The shell layer formed a porous structure through acrylic monomers and crosslinking agents, adsorbed calcium and phosphorus ions, and formed a shell layer of calcium hydrogen phosphate dihydrate to obtain ultrafine powder of core PMMA/PAA nanoparticles and shell calcium hydrogen phosphate dihydrate.

Benefits of technology

The toughness of calcium hydrogen phosphate dihydrate ultrafine powder and the binding force enhancement with the interface with the magnesium alloy are achieved, the shell thickness is increased, and the binding strength is better than that of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

According to the calcium hydrophosphate dihydrate superfine powder synthesis process, firstly, PMMA / PAA nano particles with core-shell structures are prepared through miniemulsion polymerization, a shell layer forms a three-position space network structure through polymerization of an acrylic monomer and a cross-linking agent, the shell layer is of a porous structure, the shell layer is rich in carboxyl, calcium and phosphorus ions can be adsorbed on the surfaces of the PMMA / PAA nano particles, and therefore the calcium hydrophosphate dihydrate superfine powder is obtained. And further reacting to form calcium hydrophosphate dihydrate, and covering a layer of calcium hydrophosphate dihydrate on the surface of the PMMA / PAA nano particle to obtain the calcium hydrophosphate dihydrate superfine powder with the PMMA / PAA nano particle as a core layer and the calcium hydrophosphate dihydrate as a shell layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of calcium phosphate, and in particular relates to a synthesis process of ultrafine calcium hydrogen phosphate dihydrate powder. Background Art

[0002] Calcium apatite has excellent properties such as good fluidity, low hygroscopicity, biocompatibility, a composition similar to bone mineral, and a high specific surface area. It is widely used in medicine, food, tissue engineering, biomaterials, and other fields. Calcium apatite mainly includes calcium hydrogen phosphate dihydrate (DCPD), hydroxyapatite (HA), tricalcium phosphate (α-TCP, β-TCP), calcium pyrophosphate (CPPD), tetracalcium phosphate (TTCP), octacalcium phosphate pentahydrate (OCP), amorphous calcium phosphate (ACP), and mixtures thereof. Calcium hydrogen phosphate dihydrate is a type of calcium apatite that has a similar composition and structure to human bone. It has low solubility in body fluids or plasma and is non-toxic, harmless, and non-carcinogenic when implanted in the human body. It also has excellent bioactivity, osteoconductivity, and biocompatibility. It is widely used in the repair of damaged bone tissue, root repair of alveolar ridges, hip and knee prostheses, and surface coatings for bone tissue prostheses.

[0003] Methods for synthesizing calcium phosphate dihydrate include mechanochemical, hydrothermal, chemical precipitation, and biological methods, each with its own unique characteristics. The mechanochemical method uses mechanical force to induce a direct reaction between solid-phase raw materials (such as calcium carbonate and phosphoric acid). This method requires no solvent, is environmentally friendly, allows for continuous production, and is suitable for large-scale preparation. However, particle size control is difficult, metal wear impurities can be easily introduced, and the product has low crystallinity and may contain anhydrous crystalline forms. The biological method utilizes microbial metabolism to produce acid to dissolve the phosphorus source, which then combines with calcium salts to form calcium phosphate dihydrate. While the conditions are mild and energy-efficient, the reaction cycle is long and the yield is low. The strain selection and culture conditions are complex, making industrialization difficult. The hydrothermal method promotes the directional growth of calcium phosphate dihydrate crystals in a high-temperature, high-pressure aqueous solution. The product is high in purity, crystallinity, and uniform crystalline form. However, the equipment is costly and energy-intensive, and process parameters such as pH, temperature, and time require rigorous optimization. Chemical precipitation is the most widely used method. For example, CN116812890A uses tricalcium phosphate and monocalcium phosphate as raw materials, conducts a neutralization reaction in a citric acid and sodium citrate buffer solution, and obtains calcium hydrogen phosphate dihydrate by controlling the pH value of the buffer, the solid-liquid mixing ratio, the stirring rate, and the aging time. CN103449394A first prepares an aqueous solution containing L-glutamic acid, disodium hydrogen phosphate, and sodium hydroxide, stirs at room temperature to completely dissolve them, and then adds ice, L-arginine, urea, and calcium nitrate in sequence. The stirred mixed solution is then added to a certain amount of acetone, reacted at 37°C for a period of time, cooled to room temperature, and finally reacted to obtain calcium hydrogen phosphate dihydrate. However, the obtained calcium hydrogen phosphate dihydrate is relatively brittle. Summary of the Invention

[0004] In order to overcome the problems existing in the prior art, the present invention aims to provide a process for synthesizing ultrafine calcium hydrogen phosphate dihydrate powder. The process comprises the following steps: first, preparing PMMA / PAA nanoparticles having a core-shell structure by miniemulsion polymerization; then polymerizing the shell layer by an acrylic monomer and a cross-linking agent to form a three-dimensional network structure having a porous structure; and the shell layer is rich in carboxyl groups, which can adsorb calcium and phosphorus ions on the surface of the PMMA / PAA nanoparticles. The shell layer further reacts to form calcium hydrogen phosphate dihydrate, and the surface of the PMMA / PAA nanoparticles is covered with a layer of calcium hydrogen phosphate dihydrate, thereby obtaining ultrafine calcium hydrogen phosphate dihydrate powder having a core layer of PMMA / PAA nanoparticles and a shell layer of calcium hydrogen phosphate dihydrate.

[0005] The object of the present invention is achieved through the following technical solutions: Disclosed is an ultrafine calcium hydrogen phosphate dihydrate powder having a core-shell structure, comprising core-layer PMMA / PAA nanoparticles and shell-layer calcium hydrogen phosphate dihydrate. The PMMA / PAA nanoparticles are nanoparticles prepared by miniemulsion polymerization, with a PMMA core and a PAA shell.

[0006] A process for synthesizing ultrafine calcium hydrogen phosphate dihydrate powder specifically comprises the following steps: Step 1: 15-45 parts by weight of methyl methacrylate, 1-3 parts by weight of a cross-linking agent, 1-3 parts by weight of a stabilizer, 0.5-2 parts by weight of an emulsifier, and 0.01-0.05 parts by weight of an initiator are sequentially mixed, stirred until uniformly dispersed, and ultrasonicated to prepare a pre-emulsion A; 1-5 parts by weight of methyl methacrylate, 10-25 parts by weight of sodium acrylate, 3-10 parts by weight of methacrylic acid, 3-8 parts by weight of maleic anhydride, 1-3 parts by weight of a cross-linking agent, 1-3 parts by weight of a stabilizer, 0.5-2 parts by weight of an emulsifier, and 0.01-0.05 parts by weight of an initiator are sequentially mixed, stirred until uniformly dispersed, and ultrasonicated to prepare a pre-emulsion B; Step 2: Add 1 / 3 of the pre-emulsion A and 100-200 parts by weight of deionized water to the reactor, open the inert gas, start stirring, and after 10-25 minutes, heat to 55-75°C under stirring, react for 10-30 minutes, continue to dropwise add the remaining pre-emulsion A within 15-30 minutes, and continue to react for 10-30 minutes to obtain a PMMA core layer emulsion; Step 3: Add pre-emulsion B to the PMMA core layer emulsion of step 2, complete the addition within 30-60 minutes, continue the reaction for 20-40 minutes, add the oxidant / reducing agent, keep the temperature for 30-60 minutes, cool to 35-60°C to obtain a PMMA / PAA emulsion with a core-shell structure, and add a pH adjuster to adjust the pH value to 6.0-6.5; Step 4: dissolving 30-80 parts by weight of Na2HPO4 in ionized water to prepare a 0.5M Na2HPO4 solution, and dissolving 30-80 parts by weight of CaCl2 in ionized water to prepare a 0.5M CaCl2 solution, and simultaneously adding the Na2HPO4 solution and the CaCl2 solution to the PMMA / PAA emulsion in step 3 at the same rate, and completing the addition within 60-120 minutes. The stirring reaction is continued for 90-180 minutes to generate calcium hydrogen phosphate dihydrate on the surface of the PMMA / PAA particles. The mixture is cooled, filtered, washed, and dried to obtain a calcium hydrogen phosphate dihydrate ultrafine powder having a core layer of PMMA / PAA nanoparticles with a core-shell structure and a shell layer of calcium hydrogen phosphate dihydrate.

[0007] Preferably, in step 3, the cooling temperature is 40-50° C. and the pH value is 6.1-6.3.

[0008] Preferably, the dropwise addition time in step 4 is 90-120 min, and the stirring reaction time is continued for 120-180 min.

[0009] Preferably, the co-stabilizer is one or more of hexadecane, hexadecanol, octadecane, and PVP.

[0010] Preferably, the crosslinking agent is one or more of ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, hexanediol dimethacrylate, trimethylolpropane trimethacrylate, and N,N'-methylenebisacrylamide.

[0011] Preferably, the emulsifier includes one or more of PEG, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, cetyltrimethylammonium bromide, Tween, Span, polyvinyl pyrrolidone, and chitosan.

[0012] Preferably, the initiator is one or more of APS, KPS, BPO, AIBN, AIVN, oxidizing agent / reducing agent.

[0013] Preferably, the pH adjuster is one or more of sodium citrate, hydrochloric acid, citric acid, and sulfuric acid.

[0014] The beneficial effects of the present invention are: 1) The ultrafine calcium phosphate dihydrate powder of the present invention has a core-shell structure, with PMMA / PAA nanoparticles as a core layer, and a calcium phosphate dihydrate shell layer formed on the surface of the core layer by the reaction of Na2HPO4 and CaCl2. On the one hand, the PMMA / PAA nanoparticles have a core-shell structure and, as the core layer, can improve the toughness of the ultrafine calcium phosphate dihydrate powder. On the other hand, the PAA in the shell layer of the PMMA / PAA nanoparticles can provide a large number of carboxyl groups, which can improve the binding force of the ultrafine calcium phosphate dihydrate powder to the interface of magnesium alloy and the like.

[0015] 2) The present invention provides a process for synthesizing ultrafine calcium hydrogen phosphate dihydrate powder. The process first prepares PMMA / PAA nanoparticles having a core-shell structure through miniemulsion polymerization. The shell layer is capable of forming a three-dimensional network structure with a porous structure by using acrylic monomers and a crosslinking agent. The shell layer is rich in carboxyl groups, which can adsorb calcium and phosphorus ions on the surface of the PMMA / PAA nanoparticles. Further reaction forms calcium hydrogen phosphate dihydrate, which covers the surface of the PMMA / PAA nanoparticles with a layer of calcium hydrogen phosphate dihydrate. DETAILED DESCRIPTION

[0016] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0017] The present invention will be further explained below with reference to specific embodiments.

[0018] Example 1 Disclosed is a calcium hydrogen phosphate dihydrate ultrafine powder having a core-shell structure, comprising core-layer polyacrylate nanoparticles and shell-layer calcium hydrogen phosphate dihydrate; the polyacrylate nanoparticles have a hard-core-soft-shell structure, and the shell is rich in carboxyl groups.

[0019] Its synthesis process specifically comprises the following steps: Step 1: 25 parts by weight of methyl methacrylate, 1.5 parts by weight of crosslinking agent ethylene glycol dimethacrylate, 1 part by weight of hexadecane, 1 part by weight of emulsifier sodium lauryl sulfate and 1 part by weight of PEG, and 0.03 part by weight of initiator BPO are mixed in sequence, stirred until uniformly dispersed, and ultrasonicated for 5 minutes to prepare pre-emulsion A; 3 parts by weight of methyl methacrylate, 15 parts by weight of sodium acrylate, 3 parts by weight of methacrylic acid, 5 parts by weight of maleic anhydride, 1.5 parts by weight of crosslinking agent ethylene glycol dimethacrylate, 1 part by weight of hexadecane, 1 part by weight of emulsifier sodium lauryl sulfate and 1 part by weight of PEG, and 0.03 part by weight of initiator BPO are mixed in sequence, stirred until uniformly dispersed, and ultrasonicated for 5 minutes to prepare pre-emulsion B; Step 2: Add 1 / 3 of the pre-emulsion A and 150 parts by weight of deionized water to the reactor, open the inert gas, start stirring, and after 15 minutes, heat to 55°C under stirring, react for 15 minutes, continue to dropwise add the remaining pre-emulsion A within 20 minutes, and continue to react for 25 minutes to obtain a PMMA core layer emulsion; Step 3: Add pre-emulsion B to the PMMA core layer emulsion of step 2, complete the addition within 40 minutes, continue the reaction for 30 minutes, add KPS / sodium bisulfite, keep warm for 45 minutes, and cool to 45°C to obtain a PMMA / PAA emulsion with a core-shell structure. Add sodium citrate as a pH adjuster to adjust the pH to about 6.2; Step 4: 60 parts by weight of Na2HPO4 are dissolved in ionized water to prepare a 0.5M Na2HPO4 solution, and 56 parts by weight of CaCl2 are dissolved in ionized water to prepare a 0.5M CaCl2 solution. The Na2HPO4 solution and the CaCl2 solution are simultaneously added dropwise to the PMMA / PAA emulsion in step 3 at the same rate. The addition is completed within 90 minutes, and the stirring reaction is continued for 150 minutes to generate calcium hydrogen phosphate dihydrate on the surface of the polyacrylate particles. The mixture is cooled to room temperature, filtered, washed, and dried to obtain a calcium hydrogen phosphate dihydrate ultrafine powder having a core layer of PMMA / PAA particles with a hard core and a soft shell structure and a shell layer of calcium hydrogen phosphate dihydrate.

[0020] Comparative Example 1 An ultrafine calcium hydrogen phosphate dihydrate powder was prepared according to the method of Example 1, except that pre-emulsion B was replaced by pre-emulsion A of the same mass.

[0021] Comparative Example 2 An ultrafine calcium hydrogen phosphate dihydrate powder was prepared according to the method of Example 1, except that pre-emulsion A was replaced by pre-emulsion B of the same mass.

[0022] Comparative Example 3 An ultrafine calcium hydrogen phosphate dihydrate powder is prepared according to the method of Example 1, the only difference being that maleic anhydride is replaced by sodium acrylate.

[0023] Performance Testing 1) Particle size: Malvern particle size analyzer was used for testing and characterization.

[0024] 2) XRD: Tested according to ASTM E975, compared with the standard card PDF09-0080, and analyzed the main peak position and relative intensity.

[0025] 3) TGA: According to the test standard ASTM E1131, the weight loss curve was measured at a heating rate of 10°C / min under a nitrogen atmosphere.

[0026] 4) Bonding Strength: Ultrafine calcium hydrogen phosphate dihydrate powder was dissolved in deionized water to form a 5 wt% coating solution. The magnesium alloy was immersed in the coating solution. A 10 μm coating was formed on the surface of the magnesium alloy by dip coating. The bonding strength of the coating was tested according to the test standard ASTM C633.

[0027] Table 1 Properties of ultrafine calcium phosphate dihydrate powder

[0028] From the comparison of Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the strongest peak 2θ of the ultrafine calcium phosphate dihydrate powder of Example 1 of the present invention and Comparative Example 1 and Comparative Example 2 is 11.6° and the weight loss percentage of the first endothermic peak of TGA is 20.9%. It can be seen that a calcium phosphate dihydrate shell layer is formed on the surface of the PMMA / PAA nanoparticles. The ultrafine calcium phosphate dihydrate powder prepared in Example 1 has a better effect in terms of the thickness of the calcium phosphate dihydrate shell layer and the bonding strength of the magnesium alloy. This may be because the ultrafine calcium phosphate dihydrate powder in Example 1 uses PMMA / PAA nanoparticles as the core layer, and forms calcium phosphate dihydrate on its surface through the reaction of Na2HPO4 and CaCl2. Hydrate shell. On the one hand, PMMA / PAA nanoparticles have a hard-core and soft-shell structure, and PAA has a three-dimensional network structure that can absorb water and swell. As a core layer, it can improve the tensile strength and toughness of calcium hydrogen phosphate dihydrate ultrafine powder. The carboxyl group can improve the binding force of calcium hydrogen phosphate dihydrate ultrafine powder to the interface of magnesium alloy and other materials, thereby improving the bonding strength. On the other hand, the PAA shell can provide carboxyl groups and the porosity of the three-dimensional network structure, so that more Na2HPO4 and CaCl2 are adsorbed on the surface of PMMA / PAA nanoparticles through chelation, ion action, and physical adsorption, and then react in situ to form a calcium hydrogen phosphate dihydrate shell, thereby increasing the thickness of the calcium hydrogen phosphate dihydrate shell.

[0029] From the comparison between Example 1 and Comparative Example 3, it can be seen that the strongest peak 2θ=11.6° and the weight loss percentage of the first endothermic peak of TGA of the ultrafine calcium phosphate dihydrate powder of Example 1 and Comparative Example 3 of the present invention are 20.9%, which shows that a calcium phosphate dihydrate shell layer is formed on the surface of the PMMA / PAA nanoparticles. The ultrafine calcium phosphate dihydrate powder prepared in Example 1 has a better effect in terms of the thickness of the calcium phosphate dihydrate shell layer and the bonding strength of the magnesium alloy. This may be because in Example 1, maleic anhydride can It can provide more carboxyl groups, so that more Na2HPO4 and CaCl2 are adsorbed on the surface of PMMA / PAA nanoparticles through chelation and ion action, and then react in situ to form a calcium hydrogen phosphate dihydrate shell, thereby increasing the thickness of the calcium hydrogen phosphate dihydrate shell. In addition, more carboxyl groups can make the calcium hydrogen phosphate dihydrate ultrafine powder swell to a greater extent in aqueous solution to improve tensile strength and toughness, and can also improve the bonding force between the calcium hydrogen phosphate dihydrate ultrafine powder and the magnesium alloy through the adsorption of polar groups, thereby improving the bonding strength.

[0030] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the scope of protection of the present invention.

Claims

1. A superfine calcium hydrogen phosphate dihydrate powder, characterized in that: The nanoparticles have a core-shell structure, including core PMMA / PAA nanoparticles and shell calcium hydrogen phosphate dihydrate. The PMMA / PAA nanoparticles are nanoparticles with a core of PMMA and a shell of PAA, prepared by miniemulsion polymerization.

2. A synthesis process for the ultrafine calcium hydrogen phosphate dihydrate powder according to claim 1, characterized in that: The following steps are involved: Step 1: 15-45 parts by weight of methyl methacrylate, 1-3 parts by weight of a cross-linking agent, 1-3 parts by weight of a stabilizer, 0.5-2 parts by weight of an emulsifier, and 0.01-0.05 parts by weight of an initiator are prepared into a pre-emulsion A; 1-5 parts by weight of methyl methacrylate, 10-25 parts by weight of sodium acrylate, 3-10 parts by weight of methacrylic acid, 3-8 parts by weight of maleic anhydride, 1-3 parts by weight of a cross-linking agent, 1-3 parts by weight of a stabilizer, 0.5-2 parts by weight of an emulsifier, and 0.01-0.05 parts by weight of an initiator are prepared into a pre-emulsion B; Step 2: Add 1 / 3 of the pre-emulsion A and 100-200 parts by weight of deionized water to the reactor, open the inert gas, start stirring, and after 10-25 minutes, heat to 55-75°C under stirring, react for 10-30 minutes, continue to dropwise add the remaining pre-emulsion A within 15-30 minutes, and continue to react for 10-30 minutes to obtain a PMMA core layer emulsion; Step 3: Add pre-emulsion B to the PMMA core layer emulsion of step 2, complete the addition within 30-60 minutes, continue the reaction for 20-40 minutes, add the oxidant / reducing agent, keep the temperature for 30-60 minutes, cool to 35-60°C to obtain a PMMA / PAA emulsion with a core-shell structure, and add a pH adjuster to adjust the pH value to 6.0-6.5; Step 4: Dissolve 30-80 parts by weight of Na2HPO4 in ionized water to prepare a 0.5M Na2HPO4 solution, and dissolve 30-80 parts by weight of CaCl2 in ionized water to prepare a 0.5M CaCl2 solution. Add the Na2HPO4 solution and the CaCl2 solution dropwise to the PMMA / PAA emulsion in step 3 at the same rate. Complete the addition within 60-120 minutes, continue stirring and react for 90-180 minutes, and generate calcium hydrogen phosphate dihydrate on the surface of the PMMA / PAA particles. Cool, filter, wash, and dry.

3. The process for synthesizing superfine calcium hydrogen phosphate dihydrate powder according to claim 1, wherein In step 3, the cooling temperature is 40-50° C. and the pH value is 6.1-6.

3.

4. The process for synthesizing superfine calcium hydrogen phosphate dihydrate powder according to claim 2, wherein: The dropwise addition time in step 4 is 90-120 min, and the stirring reaction time is 120-180 min.

5. The process for synthesizing superfine calcium hydrogen phosphate dihydrate powder according to claim 2, wherein: The co-stabilizer is one or more of hexadecane, hexadecanol, octadecane, and PVP.

6. The process for synthesizing superfine calcium hydrogen phosphate dihydrate powder according to claim 2, wherein: The crosslinking agent is one or more of ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, hexanediol dimethacrylate, trimethylolpropane trimethacrylate, and N,N'-methylenebisacrylamide.

7. The process for synthesizing superfine calcium hydrogen phosphate dihydrate powder according to claim 2, wherein: The initiator is one or more of APS, KPS, BPO, AIBN, AIVN, and an oxidant / reducing agent.

8. The process for synthesizing superfine calcium hydrogen phosphate dihydrate powder according to claim 2, wherein: The emulsifier includes one or more of PEG, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide, Tween, Span, polyvinyl pyrrolidone, and chitosan.

9. The process for synthesizing superfine calcium hydrogen phosphate dihydrate powder according to claim 2, wherein: The pH regulator is one or more of sodium citrate, hydrochloric acid, citric acid, and sulfuric acid.

Citation Information

Patent Citations

  • Preparation method of carboxylated nano-crystal cellulose enhanced calcium phosphate support

    CN105013018A

  • Copolymer using nano calcium phosphate coated polymethyl methacrylate as substrate and coating method thereof

    CN105315478A

  • Novel bone material substitution synthesis formula, preparation method and use method

    CN107648663A

  • PMMA / SCTP composite micro powder, preparation method of PMMA / SCTP composite micro powder, and composite bone cement using PMMA / SCTP composite micro powder

    CN109810440A

  • PMMA (Polymethylmethacrylate)-based hydration bone cement and preparation method and application thereof

    CN110339395A